Relative power and interpersonal trust - PLESSIS, Christilene Du (Institutional Knowledge at Singapore Management University, 2023)
Because trust is essential in the development and maintenance of well-functioning relationships, scholars across numerous scientific disciplines have sought to determine what causes people to trust others. Power dynamics are known to predict trust, but research on the relationship between power and trust is inconclusive, with mixed results and without systematic consideration of how the relative power distribution within dyadic relationships may influence trust in those relationships. Building on interdependence theory, we propose that both individuals in an unequal-power dyad trust each other less than individuals in an equal-power dyad because unequal-power dyads heighten the perception of a conflict of interest. We demonstrate the effect of relative power on interpersonal trust across eight main studies and 16 supplemental studies (including 12 preregistered studies; total N = 10,531), and we test the mechanism with measurement-of-mediation and moderation-of-process approaches. We confirm that the effect of power on interpersonal trust occurs only with relative power (an interpersonal manifestation of power), not with felt power (an intrapersonal manifestation). Finally, we show that the effect of relative power on interpersonal trust via conflict of interest is attenuated in the presence of intergroup competition, a theoretically motivated moderator with practical implications. Overall, the present research clarifies the relationship between relative power and interpersonal trust, suggests that high- and low-power individuals may share similar psychological experiences within the context of unequal-power relationships, and highlights the importance of considering the context in which power dynamics occur.